NEUTRONIC ANALYSIS OF DETERMINATION OF FUEL CONFIGURATION FOR HOMOGENEOUS TRIGA 2000 NEW CORE - Irsyad Irsyad; Nailatussaadah Nailatussaadah (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2022)
A neutronic analysis has been carried out to determine the configuration of fuel for the homogeneous TRIGA 2000 Reactor new core. This analysis is carried out to get the most optimal configuration scenario if all fuels used are fresh fuel by meeting the parameters in accordance with safety requirements where; shutdown margin â‰¥ $-0.5; Axial and radial Power Peaking Factor is less than 1.25 and 1.60. There are three types of homogenous core in this study that consist of three types of fuel elements; 8.5-20; 12.20 and 20-20. Method that is used in this study is count each fuel element and scenario with MCNP5 codes. Base on configuration scenarios that have been studied, we concluded that homogeneous core with 90 fuel elements with 12-20 type is the optimum one with k-eff= 1.03342.